Se ele voltar...: Getúlio Vargas e a campanha presidencial de 1950 nos traços de Hilde Weber (1949-1950) - Braga, Raiomara Lopes (2024)
The period of redemocratization that began after the end of the Estado Novo (1937-1945), more specifically the year of the 1950 presidential election, was marked by the campaign of the major Brazilian press against former president Get˙lio Vargas, who had governed Brazil from 1930 to 1945. In this research, we will seek to analyze the anti-Getulist caricatures signed by the German artist Hilde Weber (1913-1994) and published in the Rio de Janeiro newspaper Tribuna da Imprensa – an evening paper owned by Carlos Lacerda, a journalist affiliated with the Uni„o Democr·tica Nacional (UDN) and one of Vargas' main opponents –, starting from the first edition of the newspaper, published on December 27th, 1949, until the edition of October 3rd, 1950, which was published on the date of the presidential election. The time frame of the study seeks to understand the role that caricatures played during the presidential campaign, understanding that when Tribuna was launched in late 1949, the campaign to choose the candidates had already begun and, to a certain extent, the dissemination and combat of the main names had also begun. In addition to presenting how the image of Vargas – candidate for President of the Republic for the Partido Trabalhista Brasileiro (PTB) – was combated, it is necessary to present how Tribuna constructed and disseminated representations about the UDN candidate, Brigadier Eduardo Gomes, because, while Vargas was announced as the candidate of the old politics, often being associated with corruption and dictatorship, Gomes was promoted by the newspaper as the modern candidate and defender of democracy. Throughout the research, in addition to Tribuna, researched through the Digital Newspaper Library of the Biblioteca Nacional, we used as sources caricatures and articles published in other Rio de Janeiro newspapers, mainly to better present to the reader how Vargas appeared in other media outlets since his launch as a presidential candidate in 1929, thus seeking to understand how the representation of the politician in caricatures was constructed and consolidated throughout his first and long term in office. For the work with the newspapers, we had as methodological aid the research procedures in periodicals listed by Tania Regina de Luca (2008).